(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: Assessing the situation, the knowledge and practice of preventing female lower genital tract infections from 18 years old at Gia Lam General Hospital, Hanoi in 2022. Research method: Analytical cross-sectional descriptive study Results: The study subjects had general knowledge obtained about lower genital tract infections and disease prevention, the rate was 51.4%, the knowledge was not reached 48.6%. The rate of general practice obtained on prevention of lower genital tract infections has a low rate of 46.2%, not achieved at 53.8%. The analysis results show a statistically significant relationship p<0.01 between age group, place of residence, education and occupation in women related to The prevention of lower genital tract infections. There is a statistically significant relationship p<0.01 between the age group factor and the level in women related to preventing lower genital tract infections. Conclusion: Women with general knowledge accounted for 51.4%, unsatisfactory knowledge accounted for 48.6%. The rate of general practice on preventing lower genital tract infections is 46.2%, and 53.8% is unsuccessful.